РSYCHOLOGICAL SUPPORT FOR PARENTS RAISING CHILDREN WITH AUTISM SPECTRUM DISORDER (ASD) - Plyaskina,; Kokhan,; Romanova,; Skaliy,; Skaliy,; Ostrowski, (Revista Inclusiones, 2021)
A study of child-parent relations in families with children with ASD (autism spectrum disorder) and the psycho-emotional stress of parents raising children with ASD is presented. The study involved 18 parents raising children with ASD of preschool and primary school age. The technique Express diagnostics of the level of psycho-emotional tension was used to study child-parent relationships and parenting style in the family. It includes 11 scales related to violations of the parenting process, the relationship between the child and the parent. This method allows for a comprehensive approach to assessing a person's psychological and emotional stress and measures its various aspects. The authors found out the following features of the studied indicators: disharmonious in child-parent relations, the use of such styles of interaction with children by parents, such as hyperprotection, insufficient requirements, prohibitions, phobia of losing a child, minimal sanctions, projection on the child of their own undesirable qualities, emotional distance from the child, high significance of the child; a high level of psycho-emotional stress. Also, in the article, the authors present the effectiveness of the author's comprehensive program for working with parents of children with ASD. A comprehensive program of psychological support for parents of children with ASD has been developed and tested. It includes 4 main areas: psychological education, correction, individual counseling, and prevention.